Performance analysis of AES (Advance Encryption Standard) in IPSec (Internet Protocol Security) / Nik Shahidah Afifi Md Taujuddin, Abdul Hanan Abdullah and Mohd Aizaini Maarof - Md Taujuddin, Nik Shahidah Afifi; Abdullah, Abdul Hanan; Maarof, Mohd Aizaini (2006)
The Internet Protocol Security (IPSec) is a standard-based method that being used to protect the information that traverse in the Internet networking without expensive cost or complex modification on Internet application itself. But with the growth of the new technology, IPSec is subject to many treats. But the major treat of the IPSec is caused by the usage or the algorithm that has weak keys. The algorithms are DES, 3DES, Blowfish, Cast128 and RC5. These algorithms are being used as encryption algorithm in Encapsulated Security Payload (ESP) protocol. Besides, the encryption speed of these algorithms is too slow and it can only encrypt a small size data. So, to overcome these problems, this research is done to improve the security on IPSec. Throughout this research, a new algorithm from NIST that is Advance Encryption Standard (AES) is found can be used in IPSec to overcome these problems. But to make it happen, some work must be done. Initially, the framework of Internet Security Association Key Management Protocol (ISAKMP) is done. After that, the protocol is building to suite the AES in IPSec. It involve a process of initialize the ID transform value for AES and initialize the SA (Security Association) message. After that, a prototype is build to test the execution of the propose protocol. The research is then continued by doing some analysis to determine the propose protocol's performance.